Sevuparin strongly reduces hepcidin expression in cells, mice, and healthy human volunteers - Michela Asperti; Andrea Denardo; Magdalena Gryzik; Kristina E. M. Persson; Göran Westerberg; John Öhd; Maura Poli (HemaSphere)
Abstract Hepcidin is an essential regulator of systemic iron availability mediating both iron uptake from the diet and its release from body stores. Abnormally high hepcidin levels resulting from inflammation in chronic diseases cause iron restriction with the onset of anemia. Restoring physiological levels of hepcidin could contribute to ameliorating anemia in these patients. Heparin derivatives are known to suppress hepcidin expression acting on the BMP/SMAD pathway. The novel heparin derivative sevuparin, modified to markedly reduce its anticoagulant activity, is proposed as a promising hepcidin antagonizing strategy. Sevuparin was tested for its anti‐hepcidin properties in vitro in HepG2 cells, in vivo in mice, and in healthy volunteers. Sevuparin strongly suppressed basal, BMP6‐, and IL6‐dependent hepcidin expression in HepG2 cells in a dose‐ and time‐dependent manner, modulating the essential BMP6/SMAD cascade. These effects were evident in C57BL/6J mice after intravenous injection of a single dose of sevuparin (20 mg/kg) with a 70% reduction of hepcidin mRNA. Remarkably, similar effects were observed in healthy volunteers following single subcutaneous doses at 3, 6, and 9 mg/kg with 40%–50% suppression at 3 and 6 mg/kg and 72% at 9 mg/kg. Moreover, sevuparin was able to reduce hepcidin upregulation in a mouse model of acute inflammation induced by LPS, also showing an amelioration of the inflammatory markers. Combined with its excellent safety profile, these data suggest a role for sevuparin in treating high‐hepcidin disorders.